Nickel(ii) radical complexes of thiosemicarbazone ligands appended by salicylidene, aminophenol and aminothiophenol moieties1. Issue 28 (28th July 2015) - Kochem, Amélie; Gellon, Gisèle; Jarjayes, Olivier; Philouze, Christian; du Moulinet d'Hardemare, Amaury; van Gastel, Maurice; Thomas, Fabrice
<x xml:space="preserve">Abstract</x> The neutral nickel(ii) complexes are chameleon pro-radical compounds: under their one-electron oxidized form they feature an iminosemiquinonate (or iminothiosemiquinonate) radical, while under their reduced form they are α-diimine π-radicals.